Online learning and its problems in the Covid-19 emergency period - Hamid, Rimba; Sentryo, Izlan; Hasan, Sakka (Jurnal Prima Edukasia, 2020)
This study aims to obtain an in-depth overview of (1) the distribution of students at the Department of PGSD FKIP UHO based on domicile in implementing online learning during the Covid-19 period; (2) infrastructure support for the effectiveness of online learning in the Covid-19 period; and (3) students’ perceptions about online learning conducted by lecturers of the Department of PGSD FKIP UHO during Covid-19. This research was conducted in May 2020, which was included in the descriptive study, by conducting a survey of students at the Department of PGSD FKIP UHO, which was spread across all districts/cities in Southeast Sulawesi and other regions. Data collection techniques using open and closed questionnaires, with the research subjects of the class of 2017, 2018 and 2019 students who filled 316 questionnaires online from the link sent. Data obtained from students in the form of qualitative and quantitative raw data collected online and converted in Excel format. The data was processed based on the focus of this study. Based on the results of the processed data, an in-depth descriptive quantitative and qualitative analysis is carried out. The results of the study showed that: (1) Students of the Department of PGSD FKIP UHO in the online learning process were concentrated in 3 main districts/cities, namely Kendari City, Muna Regency, and Konawe Selatan Regency; (2) The main supporting factors for the effectiveness of online learning in the Covid-19 period were the carrying capacity of network access and the ability of devices to access the internet; (3) Students perceive that the implementation of online learning during the Covid-19 period has not been fully effective.